Approaches to the teme of exile and the experience of Brazilian and Argentine writers - Munhoz, Solange (Revista de Letras, 2007)
The last military coups in Argentine and Brazil had left sequels wich can be seen in those societies, being exile one of them. Among the groups that lived the exile experience, there are the writers who left their countries due to persecution of their oppositional ideas in relation to the new dominant order, or due to their search for freedor of expression. Considering these facts, our aim is to try and rescue some features from exile experience and its relation with Argentinian and Brasilian writers because its helps us to understand the treatment which has been given to the subject in a set of texts of contemporary literature production.